Аcid resistance and population structure of erythrocytes in trotter horses during and after exercise - V. I. Golovakha; О. V. Piddubnуak; S. V. Sliusarenko; L. G. Slivinska; I. A. Maksymovych; A. R. Shcherbatyy; B. V. Gutyj (Regulatory Mechanisms in Biosystems, 2017)
Regular physical exercise improves the cardiovascular system function, increases energy metabolism and antioxidant protection, provides greater muscle strength and physical endurance. However, exhaustive physical exercise can cause oxidative stress. During intense physical exercise, erythrocytes become more vulnerable to oxidative damage due to action of active oxygen forms, high concentration of polyunsaturated fatty acids. Physical loading of horses is accompanied by the development of tissue hypoxia, so one needs to study in detail changes of hematopoiesis indices, responsible for providing oxygen to tissues. When monitoring animal health, blood tests will detect a disease in early stages, because blood is a sensitive indicator of metabolic disorders, both of physiological and pathological body conditions. The purpose of present study was to examine changes of some hematopoiesis indicators (RBC, Hb, HCT, MCV, MCH), acid resistance of erythrocytesand population structure in trotting horses due to workloads of 1,600 m trot races (at rest, after race, after 90 min). In total, 20 clinically healthy horses of Orlovska and Russian trotting breeds, aged 2–3 years, were used in the study. The experimental animals included 5 mares, 15 stallions. All horses had active training. The horses were divided into two groups. The first animal group included animals that showed high results (2 min 04 s – 2 min 21 s); the second had trotters that covered the distance with worse time (2 min 28 s – 2 min 41 s). The erythrocyte couint in the leader horses after the loading increased, in the outsider horses it fell. After rest the leader horses’ erythrocytes returned to their original values, in the outsider horses they did not change. The outsider horses’ hemoglobin level after loading was lower than in the leader horses. The leader horses had higher hemoglobin content after rest (by 11.0% as compared with the values before the loading). The outsider horses had lower hemoglobin content. The leader horses hematocrit value increased, in the outsider horses ‒ decreased. The leader horses’ MCV after the loading was reduced, however after rest it recovered. The outsider horses showed MSV increase during the whole study period. The MCH in the leader horses did not change over the entire research period, in the outsider horses – it increased. The animals that showed better results, had an increasing number of “mature” and “old” erythrocytes due to their elimination from the depot. However, the outsider animals had an increasing number of “young” erythrocytes, resistant to hemolysis, but they were not able to provide tissues with needed oxygen.